2023
DOI: 10.1177/02762374221143728
|View full text |Cite
|
Sign up to set email alerts
|

The Aesthetic Emotion Lexicon: A Literature Review of Emotion Words Used by Researchers to Describe Aesthetic Experiences

Abstract: The emotions that can be considered members of the set of Aesthetic Emotions (AEs) is controversial. The present study investigated the terms used by researchers in peer reviewed studies to exemplify AEs. 100 publications from 2000–2019 exemplifying AE terms were located to produced 111 AEs which were proposed as the basis of an AE lexicon. Awe, (being) moved and wonder were reliable members and without contradiction. One fifth were negatively valenced (e.g., anger, disgust), suggesting that the presence of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…Whilst the distinction between aesthetic and utilitarian emotions is intuitive, it is hard to objectively separate them. Schubert (2024) found three aesthetic emotions to be reliably included in previous investigations without counterexamples, namely awe, (being) moved, and wonder. Even so these emotions may occur in non-aesthetic circumstances (Keltner & Haidt, 2003;Silvia, 2008).…”
Section: Aesthetic Vs Everyday Emotionsmentioning
confidence: 70%
See 1 more Smart Citation
“…Whilst the distinction between aesthetic and utilitarian emotions is intuitive, it is hard to objectively separate them. Schubert (2024) found three aesthetic emotions to be reliably included in previous investigations without counterexamples, namely awe, (being) moved, and wonder. Even so these emotions may occur in non-aesthetic circumstances (Keltner & Haidt, 2003;Silvia, 2008).…”
Section: Aesthetic Vs Everyday Emotionsmentioning
confidence: 70%
“…Representatives of ESCOM gave support and added value through their presence and keynotes, thus promoting the event. This included John Sloboda, Renee Timmers (then ESCOM president), Jane Ginsborg, and Richard Parncutt, at the first conference, and at the second conference Andrea Schiavio ( ESCOM president 2021-2024, David Dolan, Alexandra Lamont, and Heiner Gembris. The vivid response and rising interest in the Western Balkans region for the psychology of music and PAM-IE conferences resulted in the establishment of the Regional Network Psychology and Music ( RNPaM, n.d.) foundation in 2020, which now gathers colleagues and students from the countries of former Yugoslavia, with a broad interdisciplinary background.…”
Section: Background Of the Bookmentioning
confidence: 99%
“…Thereafter, they present a detailed description of three different positive aesthetic emotions within each family, which includes information on their main somatic profiles, bodily reactions, appraisals, and the most relevant triggers attributed to each aesthetic emotion by various authors. Based on Fingerhut and Prinz (2020) and Díaz-Vera (2021), Table 1 presents some of the most relevant aspects of 2 In a recent study on the aesthetic emotion lexicon, Schubert (2023) identifies 131 terms for aesthetic emotions used in scholarly sources. However, as the author admits, these results "are not in accordance with a more general population's usage of this poorly defined concept" (pp.…”
Section: Aims and Scopementioning
confidence: 99%
“…To date, the academic community has not reached a consensus on the specific categories of aesthetic emotions. However, a recent study has suggested that awe, being moved, and wonder are three typical and uncontroversial aesthetic emotions [ 15 ]. Arts engagement is a crucial pathway for inducing aesthetic emotions.…”
Section: Introductionmentioning
confidence: 99%